KONTRIBUSI PLATFORM SIBER SASTRA DALAM PEMBELAJARAN SASTRA UNTUK GENERASI NATIVE - Ayunda Nuril Chodiyah; Pradika Ayu Lestari; Darni Darni; Resdianto Permata Raharjo (Universitas Negeri Makassar, 2025)
This research aims to describe the contributions and obstacles faced during the use of cyber literature in learning literature for the native generation. This research uses the literature review method with secondary data as its research object. Secondary data is obtained from literature considered relevant to the topic through searches on several platforms such as google scholar, sinta, scopus, and researcg gate. In addition, this research also limits the data source within a five-year period from 2019 to 2024. The steps used in data analysis include identification, categorisation, thematic analysis, synthesis, and conclusion drawing. The results of the study show that the literary cyber platformis a platformthat can accommodate learning, especially in the field of literature. Literary cyber platforms are effective in increasing students' learning motivation. In addition, the literary cyber platformalso provides a place for students not only to learn to read and write, but can also be used as a medium for analysing literary texts. The analysis of literary texts is realised through the comment section provided on each platformwhere writers and readers can engage in meaningful communication. This communication is a form of analysis of the literary text presented.